Physical space of thirty pediatric intensive care units in the United States of America: a national survey - Karam, Oliver; Ahmed, Aziez; Bizzarro, Matthew; Bogue, Clifford; Giuliano, John S.; , PICU Space Collaborative; Al-Subu, Awni; Bateman, Scot; Berning, Eric; Brown, Kyle; Bulut, Yonca; Cheifetz, Ira M.; et al. (Frontiers in Pediatrics, 2024)
The design of Pediatric Intensive Care Unit (PICU) rooms significantly impacts patient care and satisfaction. The aims were first, to describe the current physical space across PICUs in the USA, and second, to identify what proportion of PICUs are compliant with current guidelines. A descriptive cross-sectional survey was conducted, targeting division chiefs and medical directors of PICUs nationwide. The survey collected data on unit type, construction and renovation dates, room sizes, and available amenities. According to the Guidelines for Design and Construction of Hospitals, PICU rooms are recommended to be single rooms, at least 200 sq ft, have a window and a private bathroom. Thirty units responded. Among the respondents, 26 had general PICUs, 9 had cardiac ICUs, and 3 had intermediate care units, with some units containing multiple types of ICUs. The median annual admissions were 1125, with a median occupancy rate of 78%. Twenty-three percent of units had at least one double room, and 3% had triple or quadruple rooms. The median room size was 265 sq ft (IQR 230; 304), the smallest room size was 220 sq ft (IQR 179; 275), and the largest single room size was 312 sq ft (IQR 273; 330). Thirty-seven percent of units had bathrooms in every room, while 80% had windows in every room. Additionally, 46% of units had dialysis capabilities in every room, and 7% had negative pressure capabilities in every room. The median building year was 2008 (IQR 2001;2014), with 36% of units having undergone at least one renovation. Larger rooms were associated with more recent build dates (p=0.01). Only 30% of the PICUs met the guidelines for physical space. These compliant units were built at a median of 4 years ago (IQR 1;8). This study highlights the variability in PICU room design and amenities across healthcare facilities. Many units still fall short of meeting the guidelines for room size, windows, and private bathrooms. Future research should investigate the relationship between room characteristics and patient outcomes to inform better design practices, with a goal of improving patient experiences and clinical outcomes.